Retail or Commissioned Live-Streaming? Mode Choice of A Platform Supply Chain Considering Consumers’ Preferences - Cheng, Juehao; Kong, Zhihong; Liu, Bin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
''live-streaming + e-commerce'' mode emerged as time required. In this paper, we aim to investigate the manufacturer’s pricing and mode choice of cooperation with a live streamer in a dual-channel live-streaming supply chain consisting of a single manufacturer, a KOL(Key Opinion Leader) live streamer, and a live-streaming platform, considering different consumers’ preferences. We depict two scenarios for the KOL streamer, retail live-streaming and commissioned live-streaming modes, in the presence of a manufacturer's self-live-streaming and investigate the optimal mode choice with the Stackelberg game. The paper discovers that under the commissioned live-streaming mode, the price of KOL live-streaming is positively (negatively) correlated with the commission ratio (consumers' preferences for the manufacturer’s self-live-streaming) and lower than that under manufacturer self-live-streaming under a low commission ratio (a high consumers' preferences for manufacturer’s self-live-streaming). In both scenarios, the KOL live-streaming’s sales effort is consistently lower than that of the manufacturer's self-live-streaming channel. Additionally, the consumer's sensitivity coefficient, the trust degree, the impact of KOL streamers, and the proportion of impulsive consumers are positively correlated with both channels' price, sales effort, and profit.